ANÁLISE DE ERROS EM QUESTÕES SOBRE SEQUÊNCIAS NUMÉRICAS: UMA CONTRIBUIÇÃO PARA A FORMAÇÃO DO PROFESSOR DE MATEMÁTICA - Heck, Miriam Ferrazza (2017)
This qualitative research had as general objective to analyze mathematics students´ difficulties when solving a question about numerical sequences, aiming at the elaboration, application and analysis of a set of activities on this content, for use on mathematics teachers training courses. A test was applied to four classes of students, two composed of academics of the mathematics teacher education courses of the two higher education courses, one by academics of an information system course of one of the institutions and, finally, a class composed by graduated in mathematics, attending a master degree in mathematics teaching at one of the institutions. The answers analysis was supported by Duval's Theory of Registers of Semiotic Representation. In addition, an interview was conducted with two professors of the mathematics teacher education course of one of the institutions, to know their opinions about the errors detected in the answers. Subsequently, a set of activities on numerical sequences was analyzed by academics of the master course, who knew the proposal of the activities on the sequence content and were invited to express their opinion on its use for the teaching of this content. After analyzing the data, it was concluded that the research reached its objectives and, in terms of registers of representation, it was noticed that the conversion of the natural language to the algebraic, in any of the items, was performed by most of the students. Conversion from natural language to figural was used as an initial resource to understand the problem. The set of proposed activities can be explored as an introduction to the study of sequences if presented in a mathematics teachers training courses, but can also be worked within the study of teaching methodologies, in initial or continuing training courses.